2022
DOI: 10.1002/aenm.202270055
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Doping Stabilized Active and Durable Sub‐2 nm Pt Nanoclusters for Low‐Pt‐Loading PEMFC Cathode (Adv. Energy Mater. 13/2022)

Abstract: PEMFCs In article number 2103144, Jia Li, Jianguo Liu and co‐workers demonstrate the underlying mechanism of cobalt doping on the unprecedented activity and durability of sub‐2 nm Pt nanoclusters. With extremely efficient utilization of Pt and superior performance in low‐Pt loading proton exchange membrane fuel cells (PEMFCs), the electrocatalysts contribute significantly to reduce the cost of PEMFCs and mitigate the dependence of hydrogen energy on precious metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…Consequently, the outstanding stability of the Co‐Rh 2 electrocatalyst stems from that Co doping reduces the total energy required to stabilize the nanoparticles. [ 51 ]…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the outstanding stability of the Co‐Rh 2 electrocatalyst stems from that Co doping reduces the total energy required to stabilize the nanoparticles. [ 51 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 36 ] For the Pt 4f state in PtCo NCs/N–CNTs‐900 in Figure S7b (Supporting Information), the lower ratio of the metallic Pt state suggests the absence of a single atom Pt and a possible durability decrease. [ 37 ] As revealed in Figure 2h and Figure S7c (Supporting Information), The C 1s spectrum for Pt SA –PtCo NCs/N–CNTs‐900 and PtCo NCs/N–CNTs‐900 exhibits three peaks, associated with graphitic C═C, C─N, and C─O, respectively. For the N 1s spectra shown in Figure 2i, there are five peaks located at 398.5, 399.2, 400.4, 401.5, and 403.6 eV, which correspond to the pyridinic N, Co─N x , pyrrolic N, graphitic N, and oxidized N states, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…and further precisely tuning its composition and structure. [ 4–14 ] It is reported that structurally ordered intermetallic Pt–M alloys exhibited a significant enhancement on ORR performance. The enhanced performance is attributed to that incorporating M atoms with a smaller atomic radius in the Pt–M alloys provides a compressive strain to Pt atoms on the surface, lowers its d‐band center, and further weakens the O 2 /intermediates adsorption, which is the rate‐determining step of ORR.…”
Section: Introductionmentioning
confidence: 99%